Do Athletes Imagine Being the Best, or Crossing the Finish Line First? A Mixed Methods Analysis of Construal Levels in Elite Athletes' Spontaneous Imagery. (April 2019) - Kacperski, Celina; Ulloa, Roberto; Hall, Craig
The purpose of this article is to illustrate data transformation in a mixed methods research phenomenological study, investigating how athletes use concrete and abstract spontaneous imagery in and around competition. To achieve this, we combined the application of co-occurring codes and numerical transformation in a novel way. A thematic analysis of qualitative interviews with 12 elite athletes identified concrete imagery to focus on strategy generation, error correction, technique, and preparation, and abstract imagery to focus on desirability, symbolic and verbal representations, and regulation of affect, arousal, and mastery. Statistical analysis identified that subjective effectiveness of imagery significantly differed for sport type (reactive/static) and competition times. Researchers wishing to apply statistical analyses to qualitative data are encouraged to employ our methodology.